Antara Rahmah dan Hegemoni: Tafsir Komunikasi Politik Islam atas Kekuasaan Turunan di Kabupaten Deli Serdang - Matondang, Abdul Rahman; Nasution, Hasyimsyah; Azhar, Anang Anas (Islam & Contemporary Issues, 2025)
This article critically interprets the intersection between prophetic Islamic values and the symbolic hegemony of dynastic power in Deli Serdang, North Sumatra. Despite procedural legality, the hereditary rule of the Tambunan family over two decades raises ethical and normative concerns. Through a qualitative case study involving document analysis, interviews, and field observation, this study finds that political communication in the region is heavily shaped by religious and cultural symbolism, which legitimizes power continuity while suppressing democratic deliberation and political regeneration. The research highlights that values such as rahmah (compassion), syura (consultation), and ?adl (justice) are often invoked rhetorically but rarely operationalized in governance practices. The study argues that Islamic political communication must transcend symbolic religiosity to promote openness, justice, and participatory leadership. Ultimately, this article offers a reinterpretation of Islamic political ethics as a critical framework to challenge symbolic domination and democratize local politics. It calls for a rethinking of democracy through Qur’anic values, exposing how structural stagnation is often disguised as political stability.